A Rust Disease on Gendarussa vulgaris Nees. Caused by Puccinia thwaitesii Berk. - Sijam, Kamaruzaman; Lim, T.K (1989)
Gendarussa vulgaris Nees., a common medicinal herb, was found to be severely infected by a rust disease. The disease was characterised by well defined, concave or convex, purplish-gray, discoloured lesions surrounded by a wide yellow halo on the adaxial surface and corresponding convex or concave lesions on the opposite abaxial surface. Infected leaves abort prematurely. The causal agent was identified as Puccinia thwaitesii Berk. The fungus produced both uredospores and teliospores on the same pustule and is a micro cyclic (hemijorm), autoecious rust.